2020
DOI: 10.1080/23311932.2020.1783173
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder market participation and its associated factors: Evidence from Ethiopian vegetable producers

Abstract: Vegetable production is mainly practiced by smallholder farmers in Ethiopia and it is their main source of income, employment opportunities and improving food security. Although farmers are producing more surplus vegetables, they are not much linked with markets and thus their opportunity to diversify their livelihoods from vegetable production is very much limited. Thus, this study was required to identify factors affecting market participation among smallholder vegetable farmers in southwest Ethiopia. To get… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 10 publications
(12 reference statements)
1
18
0
Order By: Relevance
“…More educated farmers can collect not only marketing information but also search information on the availability of agricultural inputs that helps them to produce more and supply a large amount of produce to the market. Megerssa et al (2020) also found that the educational level of the head of the household significantly influences the market participation of smallholder vegetable producers.…”
Section: The First-step Analysismentioning
confidence: 88%
See 3 more Smart Citations
“…More educated farmers can collect not only marketing information but also search information on the availability of agricultural inputs that helps them to produce more and supply a large amount of produce to the market. Megerssa et al (2020) also found that the educational level of the head of the household significantly influences the market participation of smallholder vegetable producers.…”
Section: The First-step Analysismentioning
confidence: 88%
“…The negative relationship between age and level of market participation may be due to the inability of old-aged farmers in accessing the information on inputs and marketing. Megerssa et al (2020) also reported that the age of the household head was a statistically significant factor influencing market participation among smallholder vegetable producers.…”
Section: Second Step Ols Estimation Of the Regression Modelmentioning
confidence: 97%
See 2 more Smart Citations
“…Numerous studies focus on those factors that hinder the vegetable farmers' participation in inputs and outputs markets (market integration). These studies include the farmers' socio-economic factors [ 8 ], policy variables [ 26 ], social capital [ 27 ], external agents facilitating inputs and outputs markets services [ 8 , 28 ], as well as the provision of timely information on inputs and outputs markets and credit [ 8 , 29 ]. Therefore, the success of farmers' market integration and the agriculture sector requires cooperation among farmers, market owners, policymakers, extension agents, scientists, and other stakeholders.…”
Section: Introductionmentioning
confidence: 99%